2002
DOI: 10.1074/jbc.m207584200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis by Amphiregulin via an Insulin-like Growth Factor-1 Receptor-dependent Pathway in Non-small Cell Lung Cancer Cell Lines

Abstract: Several abnormalities in the insulin-like growth factor-1 (IGF1) and erbB receptors pathways stimulate the growth and survival of lung cancer cells, but their mechanisms of action and cooperation are poorly understood. In this report, we have identified a new mechanism of apoptosis inhibition by amphiregulin through an IGF1-dependent survival pathway in non-small cell lung cancer (NSCLC) cells: amphiregulin activates the IGF1 receptor that in turn induces the secretion of amphiregulin and IGF1. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
51
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 54 publications
6
51
0
1
Order By: Relevance
“…We have previously shown that in H358 CM obtained from serum-free medium cell culture, IGF1 level was about 1 ng/ml, as usually observed in CM of other analyzed cancer cell lines, but the AR level was very high: 5 ng/ml, 50 more than in CM from other analyzed cancer cell lines (11). In all experiments performed in this paper, levels of AR and IGF1 in H358 CM were controlled as described (11) and shown to be similar.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that in H358 CM obtained from serum-free medium cell culture, IGF1 level was about 1 ng/ml, as usually observed in CM of other analyzed cancer cell lines, but the AR level was very high: 5 ng/ml, 50 more than in CM from other analyzed cancer cell lines (11). In all experiments performed in this paper, levels of AR and IGF1 in H358 CM were controlled as described (11) and shown to be similar.…”
Section: Methodsmentioning
confidence: 99%
“…In all experiments performed in this paper, levels of AR and IGF1 in H358 CM were controlled as described (11) and shown to be similar.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations